Home and ”Hygge” in Tidens Kvinder, a Popular Danish Women’s Magazine, 1930-1960 - Mechlenborg, Mette; Søberg, Martin; Bendsen, Jannie Rosenberg (Privacy Studies Journal, 2025)
Studies on the modern Western home often relate its’ origin to a particular kind of female-coded intimacy and family-oriented private space, based on new social and material norms related to the bourgeoisie. However, there has been less focus on how this archetype developed historically during mid-20th century when popular culture started to dominate mediation on home and privacy, especially in the context of modernist architecture and design. This paper explores changing concepts of the private home in the Danish popular magazine Tidens Kvinder (Today’s Women) from 1930 to 1960. By examining housing features, home portraits, expert commentary, and editorials, the article shows how ideas of the private home are entangled with discussions of modernist design and architecture, representation of interiors and broader social contexts. The paper concludes that the Danish term hygge (cosiness) was promoted as a cultural mechanism of appropriation related to home as a private space. The magazine suggested that through hygge, homemakers could assert lived space against the abstraction of planned environments of rationality, functionalism and effectiveness. Thus, hygge served as an emotional and material tool to bridge past and future – linking early bourgeois notions of the home with the lifestyle dwelling that came to characterize modern Western suburbanization. Thus, the paper adds new insights into how popular culture and notions of privacy are closely linked.